Dampak Intellectual Capital Terhadap Stabilitas Bank yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023 - Nurul Annisa; Ike Purnamasari; Muhammad Ramadhani Kesuma (Indo Publishing, 2026)
The Indonesian banking sector underwent significant transformations amidst economic volatility and the pandemic from 2019 to 2023. To survive and recover, banks were required to adapt by optimizing Intellectual Capital. This study aims to analyse the impact of Human Capital Efficiency (HCE), Structural Capital Efficiency (SCE), and Capital Employed Efficiency (CEE) on bank stability (Z-score). Utilizing a quantitative approach, this research analyses panel data from 47 conventional banks listed on the Indonesia Stock Exchange (IDX) between 2019 and 2023, selected through purposive sampling. Panel data regression analysis (EViews 12) was conducted, involving model selection tests (Chow, Hausman) and hypothesis testing (F-test and T-test). The findings reveal that only CEE exerts a positive and significant effect on the Z-score, confirming that the efficiency of physical and financial capital (tangible assets) remains the dominant determinant of a bank's financial stability. Conversely, intellectual capital components show no significant effect. HCE exhibits a positive yet insignificant impact due to the long-term nature of human resource investments, while SCE shows a negative and insignificant effect stemming from suboptimal structural capital management and limitations in the VAIC measurement formula.